Pengaruh Return On Asset,Total Aset, dan Debt To Asset Ratio Terhadap Harga Saham pada Sektor Perbankan yang Terdaftar di BEI Tahun 2020-2022 - Mohamad Yunus; Hais Dama; Idham Masri Ishak (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Mohamad Yunus, 2024. "The Influence of Profitability, Firm Size, and Leverage on Firm Value in Banking Sector Companies Listed on the IDX during 2020-2022" Bachelor’s Degre Proogram in Management, Faculty of Economics, Universitas Negeri Gorontalo. The Principal Supervisor is Dr. Hais Dama, SE, M.Si., and the Co-supervisor is Idham Masri Ishak, SE, M.Si. This research aimed to determine the influence of Profitability (ROA), Firm Size (Total Asset), and Leverage (DAR) on Firm Value (Share Price) in banking companies listed on the IDX during 2020-2022. The samples were 45 banking companies, in which the data used in this research was secondary data in the form of financial statements that banking companies had published on the Indonesia Stock Exchange (BEI). The research employed Multiple Linier Regression Analysis and Descriptive Statistics Analysis using SPSS 26 aplication data analysis. The research findings indicated that partially, Profitability (ROA) did not influence Firm Value(Share Price), Firm Size (Total Asset) influenced Firm Value (Share Price) Positively, and Leverage (DAR) influenced Firm Value (Share Price) negatively